Extracapsular dissection as sole therapy for small low-grade malignant tumors of the parotid gland - Mantsopoulos, Konstantinos; Koch, Michael; Iro, Heinrich (Laryngoscope, 2017)
OBJECTIVE: The aim of the study was to investigate whether extracapsular dissection of a primarily unsuspected lesion in the parotid gland could be oncologically sufficient for carefully selected cases of parotid gland malignomas. STUDY DESIGN: Retrospective clinical study. METHODS: The records of all patients treated for primary malignant tumors of the parotid gland solely by means of extracapsular dissection between 2006 and 2013 were studied retrospectively. Patients with manifestation of malignant tumors in the parotid gland that were not of primary salivary gland origin (squamous cell carcinomas, lymphomas, melanomas) or who had had revision surgery or other malignant tumors in their history, as well as patients with insufficient data, were excluded from our study sample. RESULTS: Nine patients, all with low-grade parotid malignancies, were detected. Our study showed acceptable oncologic and functional outcomes throughout. CONCLUSION: Our study was able to show very encouraging preliminary results following primary extracapsular dissection as sole surgical therapy for carefully selected low-stage, low-grade, inferiorly located lesions in patients with high compliance. LEVEL OF EVIDENCE: 4. Laryngoscope, 127:1804-1807, 2017.
EVALuna2:33197